Evaluation of aesthetic anteroposterior position of maxillary incisors in patients with extraction treatment using facial reference lines. Issue 7 (July 2019) - He, Danqing; Gu, Yan; Sun, Yannan
Objective: To examine whether facial reference lines could be used to evaluate the anteroposterior position of the maxillary incisors in patients that had undergone extraction treatment. Methods: The study enrolled Angle Class I patients who had favourable facial profiles after extraction treatment. Superimposition of post-treatment lateral photographs and cephalograms were constructed and anatomical landmarks on the forehead were identified. Reference lines of the forehead's anterior limit line (FALL) and the vertical line through the soft-tissue glabella (G line) were constructed. The distance between the maxillary incisors and the FALL and G line were measured. Regression analyses were performed between the maxillary incisor position and forehead inclination. Results: Forty-one patients (31 females and 10 males) were included in the study. The mean ± SD distances of the facial-axis point of the maxillary incisors (FA)–FALL and FA–G line were 1.8 ± 1.9 mm and –2.4 ± 1.8 mm, respectively. The distance of the maxillary incisors to FALL and the relative position of the maxillary incisors were both significantly correlated with forehead inclination. Conclusions: The mean position of the maxillary incisors in patients with extraction was approximately in the middle of the G line and the FALL. Correct maxillary incisor position was correlated with forehead inclination.